Research on Curriculum Teaching Reform and Practice under the OBE Concept - Li, Feng; Wang, Chen; Liu , Wenting (Journal of Educational Research and Policies, 2026)
With the continuous improvement of the higher education quality assurance system in the new era, the Outcome-Based Education (OBE) concept, focusing on learning outcomes, has gradually become a significant paradigm for promoting curriculum reform. Currently, ambiguous teaching objectives, disconnection between content and industry needs, monotonous teaching methods, and a lack of process-oriented evaluation systems are some common problems for most university curricula, therefore overall teaching quality enhancement through conceptual updates and institutional restructuring are urgently required. Based on this, using the OBE educational concept as the theoretical foundation, this paper studies curriculum teaching reform, viewing to provide a replicable and scalable model for universities to improve outcome-oriented curriculum construction systems. This research not only enriches the practical application of domestic curriculum reform using OBE concept, but also offers valuable insights for student-development-centered curriculum teaching reform in the new era.